EMIC SOCIAL WORK: A STORY OF PRACTICE - Crawford, Frances (1994)
This autoethnographical study reflects on the lived experience of a social worker with a public welfare agency in the Kimberley region of northern Western Australia during the seventies and early eighties. Framed by a philosophical consideration of the tensions between postmodernism and modernism, the study utilized the research methods of feminist critical ethnography and interpretive interactionism. Reflection on the practitioner's seven years of immersion in participant observation, interviewing and document analysis was organized around key epiphanic moments of cultural insight. In this setting, it was found that Aboriginal people were excluded from the demos in the consciousness of most Western Australians, including social workers. This actuality was traced by working from the practitioner's bodily placement in the region and the relationships this entailed. The processes by which this ideological exclusion was abstracted and generalized into standard knowledge for social workers to apply across a diversity of local situations are described. This practitioner cases-study identified the workings of structural power bases in local and particular situations, and the strong links between power and knowledge. With regard to social work, conceptual links were made to the pre-modernist critical autoethnography of Jane AddamsThe research found that to hold to a professional commitment to values it is necessary for social workers to resist seduction by and subjugation to the relations of ruling. The cultivation of a range of research philosophies rather than only the bureaucratic procedures of positivism, would allow more movement from "what is" to "what should be" in the practice profession of social work. This research argues that social work education must convey an understanding that the social can only be known by interpretation and that closure of knowledge as to the human condition is not possible. Preparing students to be able to act out of situated, reflexive home-made models of practice is named as a competency aim for social work education requiring a focus on the social construction of self, a diversity of faculty and students in open dialogue with each other, and exposure to the interpretive disciplines of anthropology/sociology, feminism, philosophy and history.